2021
DOI: 10.3390/polym13162771
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous Materials Coated Carbon Fibre Reinforced Polymer Matrix Composites

Abstract: Carbon fibre reinforced polymer composites have high mechanical properties that make them exemplary engineered materials to carry loads and stresses. Coupling fibre and matrix together require good understanding of not only fibre morphology but also matrix rheology. One way of having a strongly coupled fibre and matrix interface is to size the reinforcing fibres by means of micro- or nanocarbon materials coating on the fibre surface. Common coating materials used are carbon nanotubes and nanofibres and graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 156 publications
(213 reference statements)
0
10
0
Order By: Relevance
“…Polymer matrix composites that incorporate reinforcing particles [ 1 , 2 , 3 ], fibres [ 4 , 5 , 6 , 7 ] or fabrics [ 8 , 9 , 10 ] are of superior stability, and physical properties show enhanced robustness of the composite systems. Petroleum-derived thermoplastics are amongst the best choices for matrix materials, and the selection of reinforcing elements include but are not limited to carbonous particles or a mixture of such kinds [ 2 , 11 , 12 , 13 ], non-carbonous particles [ 14 , 15 , 16 , 17 ], carbon fibre, glass fibres and cellulose fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer matrix composites that incorporate reinforcing particles [ 1 , 2 , 3 ], fibres [ 4 , 5 , 6 , 7 ] or fabrics [ 8 , 9 , 10 ] are of superior stability, and physical properties show enhanced robustness of the composite systems. Petroleum-derived thermoplastics are amongst the best choices for matrix materials, and the selection of reinforcing elements include but are not limited to carbonous particles or a mixture of such kinds [ 2 , 11 , 12 , 13 ], non-carbonous particles [ 14 , 15 , 16 , 17 ], carbon fibre, glass fibres and cellulose fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, flexible, wearable electronic devices with superior sensing properties that can monitor the human body’s physical health, walking movement, state changes, etc., play a significant role in the field of smart products in our daily lives [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Additionally, it is important to prepare flexible composites with both excellent EMI shielding and sensing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants with either high or low molecular weight have been utilized for the chemical functionalization method [ 17 ]. Another review article reported CVD, a spray-coating method, and dip coating [ 18 , 19 ] methods using MWCNTs [ 20 ]. Pezegic et al grew MWCNTs on long continuous CF surfaces by the CVD method and to prepare a composite using these CFs with infusion molding for the evaluation of electric and thermal conductivities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%